PENGGUNAAN MUSIK DALAM PROSES PEMBELAJARANGAMBAR TEKNIK DASAR SISWA KELAS X PROGRAM STUDI BANGUNAN SMKN I TANJUNG RAYA - 278-285 , Budi Izwir (Universitas Negeri Padang, 2014)
ABSTRACT The background of this research consider steaching studentsbasic engineering drawing is boring lessons, learning outcomes which have not reached theminimum completeness criteria. The purpose ofthis study wastolook atdifferences instudent learning outcomes are give basictechnical drawing of the music that was not given to music while working on the task. This research isquasi-experimental. The populationin this study were all students in grade XBuilding Studies Program SMK Negeri I Tanjung Raya consisting of 2 classes anddirectly into a sample of the control class and experimental class. Instruments usedachievement testbased on the resultsof researchonthe influence ofmusicgetthatthere isin performingtasks such as drawingon learning outcomes ofbasicdrawingtechniques. Keywords: Music, Learning Process Basic Technical Drawing